Feminism and Gender Stereotypes in Nadzira Shafa’s Novel 172 Days: A Literary Feminist Analysis - Intan Pratami; Fera Zarianita; Vebby Andra (JPI: Jurnal Pustaka Indonesia, 2024)
Feminist literary criticism provides a framework to explore how women’s experiences, agency, and constraints are represented in literature, particularly in contexts where patriarchal values remain dominant. This study aimed to analyze the representation of feminism and gender stereotypes in Nadzira Shafa’s novel 172 Days, Aku Ikhlas Tapi Aku Rindu, a contemporary Indonesian popular literary work inspired by autobiographical experiences. A qualitative descriptive method with content analysis was employed, using the novel as the primary data source, supported by secondary literature on feminism and gender studies. Data were collected through systematic reading, annotation, and categorization of textual excerpts, which were then analyzed using feminist literary theory to identify recurring themes of women’s agency and stereotype reproduction. The findings revealed that the novel reflects feminist values through portrayals of independence, resilience, and women’s rights to education and self-expression, yet simultaneously reinforces traditional stereotypes of subordination, dependency, and negative labeling. This duality illustrates the coexistence of progressive and patriarchal discourses within contemporary Indonesian literature. The novelty of this research lies in its focus on a modern, widely read, autobiographical-inspired novel, which has received little scholarly attention in feminist criticism compared to canonical works. The results imply that popular literature can serve as a powerful medium for negotiating cultural understandings of gender, and that educators, researchers, and policymakers should pay closer attention to such texts as instruments for raising awareness of gender equality and challenging stereotypes in society.